Budget Elements of Economic Security: Specifics of Classification - О. S. Bondaruk (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2017)
Theoretical aspects of economic security in conjunction with budget components such as “budget interests” and “budget necessities” are analyzed. Key positions of the categories “budget interests” and “budget necessities” in the theory of economic security in the budgetary area are substantiated given their priority role in setting up its implementation strategy. The category “budget interests” is defined as the system of budget necessities of the interest holders, implemented through budget activities of entities and aimed at seeking benefits through the budget, in order to guarantee functioning and development of the society, the state, legal entities and physical persons. “Budget necessities” are defined as the need in budget funds to achieve and sustain, at a certain level, life activities of individuals, social groups, society, state and legal entities. Classification of budget interests by various criteria is made in the context of their impact on the economic security of the state. It is demonstrated that the four-tier classification of the budget interests by interest holder is essential to guaranteeing economic security in the budgetary area: budget interests of the state: the interests held by central and local power offices; budget interests of legal entities: the interests of profit and non-profit (public, budgetary, party and other) organizations; budget interests of individuals: basic necessities of individuals, met by budget transfers, which stand out of the array of public necessities by their individual character.